Brick and Block Masonry : Proceedings of the 16th International Brick and Block Masonry Conference, Padova, Italy, 26-30 June 2016 /: Proceedings of the 16th International Brick and Block Masonry Conference, Padova, Italy, 26-30 June 2016. (2016) - Unknown
No abstract available